Pengaruh Perbandingan Tepung Millet (Panicum milliaceum) Dan Maizena Terhadap Karakteristik Cookies - Maria Oktavia, Lourent; Pratiwi, I Desak Putu Kartika; Hapsari Arihantana, Ni Made Indri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
Abstract Cookies are a type of biscuit made from soft dough, high in fat, relatively crunchy when broken and has a solid texture. This research was aimed to find out the ratio effect of millet flour and cornstarch to the characteristic of cookies and to determine the exact ratio between millet flour and cornstarch to produce cookies with the best characteristic. The experimental design used in this research was a Completely Randomized Design with a treatment of ratio between millet flour and cornstasch that consisted of 5 levels: 100%:0%; 90%:10%; 80%:20%; 70%:30%; and 60%:40%. The treatments were repeated three times to obtain 15 experimental units. The data obtained were analyzed by analisis of variance and if the treatment had a significant effect then followed by duncan’s multiple range test. The result of research showed that the ratio between millet flour and cornstarch had a significant effect on water content, crude fiber content, starch content, color, texture, taste and overall acceptance (hedonic test), and texture (scoring test). The ratio 90%:10% of millet flour and corn starch had the best characteristic with moisture content of 4,31%, crude fiber content of 2,86%, starch content of 42,92%, color was liked, taste was liked, aroma was liked, texture was liked and crunchy, and overall acceptance was liked.